Evaluation of wireless stimulation of the endocardium, WiSE, technology for treatment heart failure. (2nd June 2016) - Seifert, M.; Butter, C.
ABSTRACT: Introduction : There are several unsolved limitations in delivering cardiac resynchronization therapy. 30-40% of patients fail to have any clinical benefit after 6 months caused by different reasons. Areas covered : Endocardial stimulation rather than conventional epicardial pacing has been shown to: be more physiologically, improve electrical stimulation of the left ventricular, give less dispersion of repolarisation and result in better resynchronization. The Wireless Cardiac Stimulation in Left Ventricle, WiCS-LV, system provides an option for wireless, left ventricular endocardial pacing triggered from a conventional right ventricular pacing spike from a co-implant. Expert commentary : The feasibility of the WiCS-LV system has been successfully demonstrated in a population of failed cardiac resynchronization patients, either failed implantation procedure of a conventional system, non-responder to conventional therapy or upgrade from pacemaker or defibrillator, where a conventional system was not an option. WiCS-LV is innovative technology with promising safety, performance and preliminary efficacy.